2016
DOI: 10.1371/journal.pone.0163984
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Plasma Triglyceride Level and Severity of Hypertriglyceridemic Pancreatitis

Abstract: BackgroundHypertriglyceridemia is the third most common cause of acute pancreatitis, but whether the level of triglyceride (TG) is related to severity of pancreatitis is unclear.AimTo evaluate the effect of TG level on the severity of hypertriglyceridemic pancreatitis (HTGP).DesignRetrospective cohort study.MethodsWe reviewed the records of 144 patients with HTGP from 1999 to 2013 at Tri-Service General Hospital. Patients with possible etiology of pancreatitis, such as gallstones, those consuming alcohol or dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 31 publications
3
40
3
Order By: Relevance
“…Besides, the severe degree of fsignificantly higher than MAP group (13.1±8.2) mmol/L. Consistently, an analysis carried by Wang et al [11] indicated that when TG > 20.0mmol/L, MSAP and SAP patients accounted for 63.1%, which was also greatly higher than MAP petients. Oh et al [12] and Yadav et al [13] believed that the occurrence and mortality rate of AP will be reduced when TG is controlled under 5.65mmom/L.…”
Section: Discussionmentioning
confidence: 52%
“…Besides, the severe degree of fsignificantly higher than MAP group (13.1±8.2) mmol/L. Consistently, an analysis carried by Wang et al [11] indicated that when TG > 20.0mmol/L, MSAP and SAP patients accounted for 63.1%, which was also greatly higher than MAP petients. Oh et al [12] and Yadav et al [13] believed that the occurrence and mortality rate of AP will be reduced when TG is controlled under 5.65mmom/L.…”
Section: Discussionmentioning
confidence: 52%
“…A retrospective study of 224 patients with HTG‐AP showed that incidence of SAP in patients with TG levels >11.3 mmol/L (1000 mg/dL) was higher as compared with patients with TG levels of 5.65‐11.3 mmol/L (500‐1000 mg/dL) . Among AP patients with TG >11.3 mmol/L (1000 mg/dL), Wang et al reported statistically significant higher incidence of local complications, moderate to severe pancreatitis and ≥3 organ failures in patients with high TG levels (>29.9 mmol/L [2648 mg/dL]) as compared with the group with low TG levels (11.3‐29.9 mmol/L [1000‐2648 mg/dL]) . However, not all studies have shown a consistent difference in the clinical course by the level of serum TG .…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia and pancreatitis due to it is not very common in pregnancy but can lead to severe complication and maternal and fetal morbidity and mortality if not diagnosed and treated timely. About 1-7% [9] of pancreatitis during pregnancy are caused due to hypertriglyceridemia and it is third common cause of pancreatitis during pregnancy after gall stone and alcoholic pancreatitis. Gestational pancreatitis in about 56% of patients is attributed to hypertriglyceridemia [9].…”
Section: Review Of Literaturementioning
confidence: 99%
“…About 1-7% [9] of pancreatitis during pregnancy are caused due to hypertriglyceridemia and it is third common cause of pancreatitis during pregnancy after gall stone and alcoholic pancreatitis. Gestational pancreatitis in about 56% of patients is attributed to hypertriglyceridemia [9].…”
Section: Review Of Literaturementioning
confidence: 99%